Analisis Pengambilan Keputusan untuk Pabrik Sepatu ABC - Widya Nurcahayanty Tanjung; Adhitya P; Ajeng Putri; Dian R.; Dwiyogo Adiprasetyo; Tiara Juanita (Universitas Bunda Mulia, 2017)
Strategy is the most important thing in a company. Because of the importance of the matter, the determination of the strategy should be done carefully and based on the position and condition of the company is situated. There are many methods to make corporate decisions. At this time the lab, used five different methods of decision-making, such as decision tree method, Bayes methods, methods Comparison Matrix Exponential, Comparative Performance Index method, and the latter is the Delphi method. From the observations done in Karinda PT Kharisma, the main strategy is taken market development strategy. While the results obtained from the mapping of the decision tree strategy is the addition of a new segment. For subsequent information made six alternative methods and criteria that support 4. The alternative is to segment the capital on the island of Java, namely Semarang, Surabaya, Jakarta, Serang, Bandung, and Yogyakarta. Of all the methods that do the same segmentation is obtained to Jakarta.Keywords: Analyze of Decision Making, Decision Tree Method, Bayes Methods, Comparison Matrix Exponential Methods, Comparative Performance Index Method, Delphi Method